English as a medium of instruction - a growing global phenomenon - Dearden, J (British Council, 2014)
This report is an attempt to set out a global view of English Medium Instruction today. It is a bird's eye view or a snapshot of the views and issues involved when implementing EMI. The report is based on a recent worldwide survey conducted with British Council staff acting as informed respondents and covers 55 countries; countries which are promoting, resisting or sometimes even reversing EMI in schools and universities.